Pengenalan Quotes Sebagai Strategi Pemasaran Digital Pada Produk Gula Aren Desa Branjang - Oktaga, Andreas Tigor; Yoki Nawan Gunara; Umi Fadlilah Hidayanti; Aji Priyambodo; Prihati; Agus Ariawan (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2025)
This Community Service activity was driven by the low adoption of digital marketing strategies among palm sugar-producing MSMEs in Branjang Village, Semarang Regency, Central Java. These MSMEs still rely on conventional marketing methods and have not fully utilized digital tools to communicate product value. The main goal of this program was to enhance the capacity of MSME actors to create emotionally and culturally relevant digital content using quotes. The method applied was a community-based participatory educational approach, starting from needs assessment to contextual quote creation training. The results showed that the quote-based strategy successfully increased awareness among MSME actors about the importance of emotional narratives in building product identity and consumer engagement. Significant shifts were observed in participants’ perceptions of social media, new initiatives to document production processes emerged, and meaningful quotes were developed reflecting the uniqueness and cultural values of local palm sugar. This approach was found to be effective, simple, and inclusive, bridging technical limitations with strong local potential.